2010
DOI: 10.1021/jm901501s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activities of 2-Amino-1-arylidenamino Imidazoles as Orally Active Anticancer Agents

Abstract: 2-Amino-1-arylidenaminoimidazoles, a novel class of orally (po) active microtubule-destabilizing anticancer agents, were synthesized. The compounds were designed from a hit compound identified in a drug discovery platform by using cancer cell-based high throughput screening assay. Selective synthesized compounds exerted cell cytotoxicity against human cancer cells. The underlying mechanisms for the anticancer activity were demonstrated as interacting with the tubulins and inhibiting microtubule assembly, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Considering the fact that the series of Imidazol compounds are brand new [2] and the defects in the drugs available, results in defragmentations and breaks in the DNA string [3], the need for finding ways to cope with that problem felt more than ever, on the other hand, because the string of DNA containing the nucleotide sequence is repeated sequentially [4], it is logical to limit the study to this strands and making the calculations simpler. Considering these points in this study, four nucleotides (Adenine, Cytosine, Guanine and Thymine) examined by using accurate Quantum Mechanical methods and the base optimum structure of these nucleotides investigated under the influence of the drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the fact that the series of Imidazol compounds are brand new [2] and the defects in the drugs available, results in defragmentations and breaks in the DNA string [3], the need for finding ways to cope with that problem felt more than ever, on the other hand, because the string of DNA containing the nucleotide sequence is repeated sequentially [4], it is logical to limit the study to this strands and making the calculations simpler. Considering these points in this study, four nucleotides (Adenine, Cytosine, Guanine and Thymine) examined by using accurate Quantum Mechanical methods and the base optimum structure of these nucleotides investigated under the influence of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…Selective synthesized compounds exerted cell cytotoxicity against human cancerous cells. These new po active antimitotic anticancer agents are to be further examined in preclinical studies and developed for clinical uses [2]. Scheme 1 shows the general method for the synthesis of 2-amino-1-arylidenaminoimidazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that compounds containing an amino imidazole structure possess anticancer activities [17,18]. Further modified from the chemical skeleton of this hit compound, novel core chemical scaffolds containing amino imidazole have been designed and a number of the structural derivatives have been synthesized and evaluated their anticancer activities, including a novel class of orally active anticancer agents 2-amino-1-arylidenamino imidazoles previously reported [19]. These 2-amino-1-arylidenamino compounds consist of an (E)-exocyclic imine with acceptable chemical stability for exerting proper oral bioavailability and thus the in vivo activities [19].…”
Section: Introductionmentioning
confidence: 99%
“…Further modified from the chemical skeleton of this hit compound, novel core chemical scaffolds containing amino imidazole have been designed and a number of the structural derivatives have been synthesized and evaluated their anticancer activities, including a novel class of orally active anticancer agents 2-amino-1-arylidenamino imidazoles previously reported [19]. These 2-amino-1-arylidenamino compounds consist of an (E)-exocyclic imine with acceptable chemical stability for exerting proper oral bioavailability and thus the in vivo activities [19]. Nonetheless, imine moiety could be metabolized by liver microsomal enzymes in vivo [20] and the imine metabolic mechanism has been utilized to design prodrugs [21].…”
Section: Introductionmentioning
confidence: 99%